A comparative clinical study of Siravedha and Agnikarma in management of Gridhrasi (sciatica) - Vaneet Kumar, J. (Ayu, 2014)
BACKGROUND: Lifetime incidence of low back pain is 50-70% and incidence of clinically significant sciatica due to lumbar disc prolapse occurs in 4-6% of the population. Low back pain and sciatica is major cause of morbidity throughout the world. There is only conservative treatment giving short-term relief in pain or surgical intervention with side-effect. There is need to find out quick relief from pain in today's era as it affects physical as well as mental and social life of patients. In Ayurveda, various modalities are given but Agnikarma and Siravedha are supposed to give instant relief from pain. AIMS: To compare the efficacy of Agnikarma and Siravedha in the management of Griidhrasi. MATERIALS AND METHODS: It's an open randomized parallel group trial. A total of 30 patients, divided randomly in two groups, were treated by Agnikarma in 19 patients and Siravedha in 11 patients. Agnikarama was done at lumbosacral spine and Achilles tendon region by Panchadhatu Shalaka. Siravedha was done from four Angulas below Janu Sandhi (Knee joint). Placebo starch capsules were given to all patients. Paired t-test applied for efficacy within the group and Chi-square test to compare the efficacy of two groups. RESULTS: Individually both groups had given relief in cardinal symptoms of Gridhrasi. 68.42% patients showed marked improvement and 21.05% had complete relief after Agnikarma. In Siravedha, 72.73% patients had moderate improvement whereas 27.27% patient had marked improvement. CONCLUSION: Agnikarma gives better effect than Siravedha in management of Gridhrasi.